2009
DOI: 10.1002/app.31075
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of 1‐oxo‐2,6,7‐trioxa‐1‐phorsphabicyclo[2,2,2]oct‐4‐yl methyl acrylate and (10‐oxo‐10‐hydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐yl) methyl acrylate with styrene and their thermal degradation characteristics

Abstract: Two phosphorus-containing acrylates of 1-oxo-2,6,7-trioxa-1-phorsphabicyclo[2,2,2]oct-4-yl methyl acrylate and (10-oxo-10-hydro-9-oxa-10k 5 -phosphaphenanthrene-10-yl) methyl acrylate were free-radical-copolymerized with styrene (St). The r 1 reactivity ratio values (related to the novel acrylates) were 0.342 and 0.225, respectively, and the r 2 reactivity ratio values (related to St) were 0.432 and 0.503, respectively. The thermal stability of the copolymers was tested by thermogravimetric analysis (TGA) in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…In the NMR spectrum of BC 2 NP 2 , the methylene resonance in ethyl groups appeared at 4.02, 2.96, and 2.84 ppm, and the doublets of ‐CH 2 vinylic pattern appeared at about 6.16 and 5.65 ppm and the chemical shift at 5.87 ppm was attributed to CH. Moreover, the methoxy protons appeared at 3.51 ppm . The above results confirmed that HOC 2 NP 2 and BC 2 NP 2 have been successfully prepared by Kabachnik‐Fields reaction, esterification, and acylation reaction.…”
Section: Resultssupporting
confidence: 63%
“…In the NMR spectrum of BC 2 NP 2 , the methylene resonance in ethyl groups appeared at 4.02, 2.96, and 2.84 ppm, and the doublets of ‐CH 2 vinylic pattern appeared at about 6.16 and 5.65 ppm and the chemical shift at 5.87 ppm was attributed to CH. Moreover, the methoxy protons appeared at 3.51 ppm . The above results confirmed that HOC 2 NP 2 and BC 2 NP 2 have been successfully prepared by Kabachnik‐Fields reaction, esterification, and acylation reaction.…”
Section: Resultssupporting
confidence: 63%
“…There is a wide range of organic P-containing FRs available including phosphates, phosphonates, polyphosphonates, hybrid metal phosphonate salts, etc. [ 5 , 38 , 41 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. The mechanism and the efficiency of FRs depend not only on the chemical structure of a P-bearing compound itself, but also on its interaction with the polymeric backbone during pyrolysis and combustion.…”
Section: Fire Retardation Of Styrenic Polymers With Phosphorous-comentioning
confidence: 99%
“…An effective method to overcome this shortcoming is to modify the structure of DOPO with other known FRs or to incorporate them during polymerisation processes in the presence of other reactive monomers. The most commonly used method is the chemical modification of DOPO through the reaction with paraformaldehyde, which resulted in the formation of 2-(6-oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)methanol (ODOPM), as shown in Figure 20 [ 48 , 113 , 114 ].…”
Section: Fire Retardation Of Styrenic Polymers With Phosphorous-comentioning
confidence: 99%
“…IFRs, which combine an acid source, a blowing agent, and a char-forming agent within one molecule, have received more and more attention. [2][3][4] A halogen-free IFR, pentaerythritol spirobisphosphoryl dicyandiamide (SPDC), which has a ratio of phosphorus, nitrogen, and carbon of 1.00:1.81:2.13, was reported to have a char yield of 39.2 wt % at 600 C in nitrogen. 5 Polypropylene (PP) with 30 wt % SPDC addition passed the UL-94 V-0 rating and showed a limiting oxygen index (LOI) value of 32.5, and the tensile strength, flexural strength, and notched Izod impact strength decreased only by 4.0, 8.1, and 11.4%, respectively, as compared with those of neat PP.…”
Section: Introductionmentioning
confidence: 99%
“…2,11,12 The absorptions at 3352 and 3122 cm 21 corresponded to the stretching vibrations of NAH, 13,14 and those at 1540 and 1396 cm 21 were the signals for the vibrations of the triazine ring. 15 The absorption at 781 cm 21 was assigned to the PAN stretching band; 16 this indicated that melamine was also introduced into the target product of EADP.…”
mentioning
confidence: 99%